Synoptic Analysis: Teachers’ Commitment in Nigeria - Jibril Almustapha; Abbas Sani Dahiru; Anas Hamisu Lawal (Journal of Social Science, 2023)
This study attempts to analyse the extent of teachers’ commitment among secondary schools of Zamfara State, Nigeria. The study was designed as descriptive research. Population of the study consisted of 28 Public Secondary Schools in Gusau Local Government Area of Zamfara State with a total number of 367 in-service teachers. From the population of the study, 19 Public Secondary Schools were sampled, wherein 190 teachers were extracted as participants in the study through simple random sampling technique using Morgan and Krejcie’s (1971) table of determining sample size. A structured questionnaire titled ‘Teacher Commitment Questionnaire’ with 15 items developed by Allen (1997) which was constructed on a 4-point Likert scale was employed as an instrument for data collection. Data analysis was made through descriptive statistics using mean and standard deviation. The paper portrayed that, teachers’ commitment towards teaching profession among public secondary schools of Zamfara State was on moderate extent with reference to its average mean value of (M=2.62, SD=1.61). This paper recommends that, in order to improve teachers’ commitment, more efforts should be offered by the stakeholders in education sector for ensuring a positive adjustment of successful course delivery of teachers and most importantly the academic achievement of the learners.